Faktor-Faktor yang Berhubungan dengan Kejadian Stunting di Kabupaten Nganjuk - Mirasa, Yudied Agung; Umami, Aininta; Arifatul Mu’awanah, Siti; Sunardi, Sunardi (Jurnal Sehat Mandiri, 2023)
Stunting is a condition that describes chronic malnutrition during a period of growth and development from the beginning of life. The incidence of stunting in Nganjuk Regency is 20% in 2022. The aim of this research is to find out the factors that influence the incidence of stunting in Nganjuk Regency. The type of research used is analytic observational with a cross sectional approach. The research sample was 275 respondents from 966 toddlers who were taken by simple random sampling technique. The data analysis used was univariate and bivariate analysis using the Chi Square test. The risk factors that were jointly proven to have a relationship with the incidence of stunting in Nganjuk Regency were work (p=0.001 and aPOR=2.89), family income (p=0.000 and aPOR=6.26), history of exclusive breastfeeding (p= 0.000 and aPOR=3.36), history of LBW (p=0.002 and aPOR=2.62), and feeding pattern (p=0.018 and aPOR=1.52). Meanwhile, the variables that were not related to the incidence of stunting were education (p=0.752 and aPOR=1.13). In conclusion, the variables associated with the incidence of stunting are employment, family income, history of exclusive breastfeeding and history of LBW. Based on the results of the research, suggestions that can be given are to increase routine monitoring of the implementation of PMT for pregnant women who have been given, as well as education when pregnant women visit the puskesmas.